Satisfaction with life in workers: A chained mediation model investigating the roles of resilience, career adaptability, self-efficacy, and years of education - Topino, Eleonora; Svicher, Andrea; Di Fabio, Annamaria; Gori, Alessio (Frontiers in Psychology, 2022)
Satisfaction with life is a core dimension of well-being that can be of great importance in the workplace, in light of the close link between worker health and organizational success highlighted by the perspective of Healthy organizations. This study aimed at analysing the factors associated with satisfaction with life, focusing on the role of resilience, career adaptability, self-efficacy, and years of education. A sample of 315 workers (67% women; Mage = 34.84 years, SD = 12.39) filled out the Satisfaction with Life Scale, General Self‐Efficacy Scale, Career Adapt-Abilities Scale, the 10-item Connor-Davidson Resilience Scale, and a demographic questionnaire. Data were analyzed by implementing a chained mediation model. Results showed a significant and positive relationship between resilience and satisfaction with life, partially moderated by the chained effect of career adaptability and self-efficacy, controlling for education. When inserted as a covariate, education showed a significant and negative association with satisfaction with life. Such findings contribute to enriching the field of research on the factors that contribute to the well-being of workers and may have important practical implications for interventions in organizations.